Preparation method and application of layered positive electrode material with ternary gradient composite coating structure

通过采用三元梯度复合包覆结构的层状正极材料制备方法,结合低温等离子体合成技术和改性液改性处理,解决了现有三元正极材料工艺成本高、容量低、循环保持率低及 The problem of fast internal resistance has achieved high -capacity, good circulation performance and low internal resistance materials, which significantly improves the electrochemical properties and long -term stability of lithium ion batteries.

CN119349652APending Publication Date: 2025-01-24山西工程科技职业大学
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411467606.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing ternary cathode materials have high process costs, low capacity performance, low cycle retention rate and high internal resistance growth, which seriously restrict the large-scale production and application of lithium-ion batteries.

Method used

The preparation method of layered cathode materials using a ternary gradient composite coating structure is achieved by fully stirring and mixing in deionized water, combined with low-temperature plasma synthesis technology and modification liquid modification treatment, to form high stability and high electrochemical properties. Performance materials.

Benefits of technology

The high -capacity, good circulation performance, low internal resistance and high voltage characteristics of the material are realized, which significantly improves the electrochemical properties and long -term stability of lithium -ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349652A_ABST
    Figure CN119349652A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a layered positive electrode material with a ternary gradient composite coating structure, which comprises the following steps: placing NiO, Co3O4, MnO2 and Li2CO3 in deionized water, fully stirring and uniformly mixing, and then drying in an air dry oven to obtain a mixed dry matter I after drying; the novel ternary positive electrode material provided by the invention has the advantages of high capacity, good circulation, low DCR increase and good high voltage resistance. According to the design of the novel ternary positive electrode material, a new material synthesis process and technical innovation are utilized, and the capacity and the cycle performance of the material are effectively improved by optimizing the microstructure of the material and an ingenious interface structure coating design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of layered positive electrode materials, and in particular to a preparation method and application of a layered positive electrode material with a ternary gradient composite coating structure. Background Art

[0002] In today's society, as energy and environmental problems become increasingly serious, the development of renewable energy technology and devices has become a hot topic of concern for scientists from all over the world. As a new generation of energy storage devices, lithium-ion batteries have become the mainstream energy storage capacity devices in the fields of electronic products, smart phones, electric vehicles, etc., and ternary cathode materials, as an important component of lithium-ion batteries, have also attracted attention from all countries for their synthesis technology. However, the currently commercialized ternary cathode materials have serious problems such as high process cost, low capacity utilization, low cycle retention rate, and high internal resistance growth, which seriously restrict the large-scale production and application of lithium-ion batteries. Therefore, it is urgent to develop a ternary cathode material with low process cost, high capacity, good cycle and low DCR growth. Therefore, the lithium-ion battery industry can be further developed by overcoming the following problems: the traditional calcination process of ternary cathode materials has a long synthesis cycle, high energy consumption, high process cost, and low production efficiency, which seriously restricts production capacity; the traditional high-temperature calcination process has poor grain growth control, uneven crystal growth, and low crystallinity, resulting in a low degree of single crystallization of the material and an unstable matrix structure, which leads to the dissolution of transition metal ions and the destruction of the crystal structure, resulting in material failure; the traditional dry mixing method has a low interface bonding force between the metal oxide and the matrix particles, and the interface impedance will increase. At the same time, the traditional inverted coating cannot effectively block the electrolyte, reducing the electrochemical performance of the material;

[0003] The production and preparation of ternary positive electrode materials in the industry is mainly carried out by dry mixing and long-term high-temperature roasting in oxygen or air for large-scale production. It not only has high energy consumption and low production efficiency, but also has high requirements for the process manufacturability of the equipment, which seriously restricts the economic effect. In the current international environment and industry background, people's extreme pursuit of cost and performance (such as energy density, cycle life, DCR growth, etc.) makes it necessary to develop a low-cost, high-performance lithium-ion battery positive electrode ternary material from the preparation process. The high-temperature solid-phase doping and low-temperature coating technologies currently adopted by the industry cannot fundamentally solve the cost and performance problems of ternary positive electrode materials. Therefore, it is urgent to develop a ternary positive electrode material with low process development cost and better performance. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing and applying a layered positive electrode material with a ternary gradient composite coating structure to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a layered positive electrode material with a ternary gradient composite coating structure, comprising the following steps:

[0007] (1) NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 Place in deionized water and stir to mix thoroughly, then dry in a blast drying oven to obtain a mixed dry product I; wherein NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 The mass is measured according to the molar ratio of the prepared ternary positive electrode material; the drying temperature in the blast drying oven is 120°C to 180°C, and the drying time is 4h to 8h;

[0008] (2) placing the dried object I in a plasma generator tube furnace device;

[0009] (3) generating plasma by adjusting the frequency and power of the radio frequency power supply, raising the temperature in the tube furnace to 700° C. to 850° C. and maintaining the temperature for 30 min to 180 min, then turning off the radio frequency power supply and cooling the temperature to room temperature to obtain a single crystal ternary cathode material II;

[0010] (4) placing the single crystal ternary cathode material II and the coating source A in deionized water, stirring and mixing them evenly, and then drying them in a forced air drying oven to obtain a mixed dried product III;

[0011] (5) evenly spreading the dried material III into a boat-shaped sagger, and repeating steps 2) and 3) to obtain a single crystal ternary positive electrode material IV; wherein the temperature in step 3) is 200° C. to 350° C., and the holding time is 20 min to 120 min;

[0012] (6) Screening, demagnetizing and packaging the material IV to obtain the final product.

[0013] Preferably, the drying temperature in step 1) is 150°C and the drying time is 6 hours; the NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 The mass is measured according to the molar ratio of Li:Ni:Co:Mn=0.7:0.1:0.2:1.0.

[0014] Preferably, the specific operation steps of placing the dried object I in the plasma generator tube furnace device are:

[0015] Evenly spread it into the boat-shaped sagger, and then place the sagger containing material I in the middle position of the plasma generator tube furnace, and then lock and seal the plasma generator tube furnace device; open the oxygen valve connected to the plasma generator tube furnace to make the material I in the generator tube furnace in the oxygen atmosphere; wherein, the boat-shaped sagger is a high-temperature refractory ceramic sagger, the oxygen intake flow rate is 10 to 200 liters / min, and the tube furnace pressure is 0Pa to 30Pa.

[0016] Preferably, the oxygen intake flow rate is 95 liters / min, and the tube furnace pressure is 25 Pa; the temperature in the tube furnace in step 3) is raised to 780° C. and kept warm for 90 minutes.

[0017] Preferably, the coating source A includes but is not limited to Al 2 O 3 、Al(OH) 3 、TiO 2 , ZnO, Y 2 O 3 、MgO、WO 3 、ZrO、Co 3 O 4 One or more of the coating source A accounts for 0.05% to 0.50% of the mass ratio of the single crystal ternary positive electrode material III.

[0018] Preferably, the coating source A is Al2O3 and TiO2; the mass ratio of Al2O3 to TiO2 is 1.2:1.0, and the mass ratio of Al2O3 and TiO2 to the single crystal ternary positive electrode material III is 0.17%;

[0019] In step 5), the temperature in the tube furnace is raised to 290° C. and kept at this temperature for 60 min.

[0020] Preferably, the coating source A is also modified by a modifying liquid, and the specific modification method is:

[0021] Preparation of modified solution:

[0022] 3-5 parts of silane coupling agent KH560 are added to 6-10 parts of chitosan solution with a mass fraction of 4-6%, and then 1-3 parts of yttrium nitrate solution with a mass fraction of 2% and 2-5 parts of nano-silicon dioxide modifier are added to fully mix to obtain a modified solution;

[0023] The coating source A and the modified liquid are stirred and modified in a weight ratio of 4:7. After the stirring is completed, the mixture is filtered and dried.

[0024] Preferably, the preparation method of the nano-silicon dioxide modifier is: irradiating the nano-silicon dioxide in a proton irradiation box for 5-10 minutes, the irradiation power is 350W, and after the irradiation is completed, immersing the irradiated nano-silicon dioxide in a sufficient amount of 5% by mass lanthanum chloride solution for immersion treatment, and after the immersion is completed, filtering and drying to obtain the nano-silicon dioxide modifier.

[0025] Preferably, the immersion power is 350-400W and the immersion time is 5-10 minutes.

[0026] The present invention also provides a method for preparing a layered positive electrode material with a ternary gradient composite coating structure and its application in lithium-ion batteries.

[0027] Plasma technology is a technology based on the principles of plasma physics. It uses the high energy and chemical properties of plasma to achieve various applications in many fields and is often used for material synthesis and surface modification. In the processing and modification of lithium-ion battery materials, the plasma technologies that can be used include glow discharge plasma treatment, magnetron plasma sputtering, and plasma enhanced chemical vapor deposition. These technologies are applied to material processing, mostly based on free radical chemistry. Normally, free radicals are in the ground state, but some free radicals always exist in the form of electronic excited states, which have higher energy than ground state free radicals and can break a variety of chemical bonds. The plasma intensity can be adjusted by controlling the power supply RF frequency, power, and gas flow (pressure) to effectively trigger selective chemical reactions, and is used for doping and surface coating of lithium-ion battery positive electrode materials;

[0028] The wet mixing process can fully and evenly mix lithium salts and metal oxides. The uniform mixing of reactants can make the material react and grow quickly, forming a phase structure with good crystallinity and uniform crystal phase; the plasma source preparation technology reduces the temperature of the reaction system and energy consumption, which can greatly reduce costs and increase efficiency. In the plasma system,

[0029] The excited electrons have high temperature characteristics and a high migration rate. When they collide at high speed, they produce thermal effects inside the material, thereby improving the reaction efficiency, reducing the stability and time required for the reaction, greatly reducing the reaction energy consumption, and reducing the process cost; the plasma source preparation technology improves the uniformity and density of the particle surface coating, and effectively blocks the erosion of the electrolyte on the matrix particles, thereby improving the electrochemical properties of the material; at the same time, the modified liquid modification treatment is adopted, with nano-silica modifier combined with silane coupling agent KH560, chitosan solution and yttrium nitrate solution and other raw materials to enhance the interface of the product raw materials, improve the performance effect of the product system, and further improve the performance effect of the product.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention solves the problems of high energy consumption, low efficiency and low electrochemical performance of traditional ternary materials, and designs a new ternary positive electrode material with high capacity, good cycle, low DCR growth, and good high voltage resistance. The design of the new ternary positive electrode material utilizes new material synthesis processes and technological innovations. By optimizing the microstructure of the material and the clever interface structure coating design, the capacity and cycle performance of the material are effectively improved, while the growth rate of the material internal resistance and DCR is reduced. In addition, the material also has good resistance to high voltage and electrolyte corrosion, and can still maintain good performance under high voltage, providing reliable guarantee for the long-term stable operation of lithium-ion batteries, and is expected to promote further upgrading of lithium-ion battery technology.

[0032] The present invention uses low-temperature plasma synthesis technology, which can not only greatly reduce the reaction temperature and reaction time, improve production efficiency and reduce energy consumption, but also the plasma source preparation technology can improve the grain growth rate, further improve the degree of crystallization of the material, the roundness and size uniformity of the particles, and greatly improve the electrochemical properties of the material; through plasma technology coating, the electrons excited by the plasma source can help the particles to grow regularly in a strong electric field, so that the particles have uniform size distribution and roundness and form a dense and stable coating layer, which fully avoids the disadvantages of existing metal oxide coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A device diagram of a "plasma generator tubular furnace" for a highly efficient method for preparing positive electrode materials for lithium-ion batteries provided by the present invention.

[0034] Figure 2 This is a SEM photograph of the lithium-ion battery single crystal ternary positive electrode material prepared in Optimization Example 1 of the present invention.

[0035] Figure 3 This is a SEM photograph of the lithium-ion battery single crystal ternary positive electrode material prepared in Comparative Example 1 of the present invention.

[0036] Figure 4 This is an XRD comparison diagram of the lithium-ion battery single crystal ternary positive electrode material prepared in Optimization Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] A method for preparing a layered positive electrode material with a ternary gradient composite coating structure in this embodiment includes the following steps:

[0039] (1) NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 Place in deionized water and stir to mix thoroughly, then dry in a blast drying oven to obtain a mixed dry product I; wherein NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 The mass is measured according to the molar ratio of the prepared ternary positive electrode material; the drying temperature in the blast drying oven is 120°C to 180°C, and the drying time is 4h to 8h;

[0040] (2) placing the dried object I in a plasma generator tube furnace device;

[0041] (3) generating plasma by adjusting the frequency and power of the radio frequency power supply, raising the temperature in the tube furnace to 700° C. to 850° C. and maintaining the temperature for 30 min to 180 min, then turning off the radio frequency power supply and cooling the temperature to room temperature to obtain a single crystal ternary cathode material II;

[0042] (4) placing the single crystal ternary cathode material II and the coating source A in deionized water, stirring and mixing them evenly, and then drying them in a forced air drying oven to obtain a mixed dried product III;

[0043] (5) evenly spreading the dried material III into a boat-shaped sagger, and repeating steps 2) and 3) to obtain a single crystal ternary positive electrode material IV; wherein the temperature in step 3) is 200° C. to 350° C., and the holding time is 20 min to 120 min;

[0044] (6) Screening, demagnetizing and packaging the material IV to obtain the final product.

[0045] The drying temperature in step 1) of this embodiment is 150° C. and the drying time is 6 hours; the NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 The mass is measured according to the molar ratio of Li:Ni:Co:Mn=0.7:0.1:0.2:1.0.

[0046] The specific operation steps of placing the dried object I in the plasma generator tube furnace device of this embodiment are:

[0047] Evenly spread it into the boat-shaped sagger, and then place the sagger containing material I in the middle position of the plasma generator tube furnace, and then lock and seal the plasma generator tube furnace device; open the oxygen valve connected to the plasma generator tube furnace to make the material I in the generator tube furnace in the oxygen atmosphere; wherein, the boat-shaped sagger is a high-temperature refractory ceramic sagger, the oxygen intake flow rate is 10 to 200 liters / min, and the tube furnace pressure is 0Pa to 30Pa.

[0048] In this embodiment, the oxygen intake flow rate is 95 liters / min, and the tube furnace pressure is 25 Pa; the temperature in the tube furnace in step 3) is raised to 780° C. and kept warm for 90 minutes.

[0049] In this embodiment, the coating source A includes but is not limited to Al 2 O 3 、Al(OH) 3 、TiO 2 , ZnO, Y 2 O 3 、MgO、WO 3 、ZrO、Co 3 O 4 One or more of the coating source A accounts for 0.05% to 0.50% of the mass ratio of the single crystal ternary positive electrode material III.

[0050] The coating source A in this embodiment is Al2O3 and TiO2; the mass ratio of Al2O3 to TiO2 is 1.2:1.0, and the mass ratio of Al2O3 and TiO2 to the single crystal ternary positive electrode material III is 0.17%;

[0051] In step 5), the temperature in the tube furnace is raised to 290° C. and kept at this temperature for 60 min.

[0052] The coating source A of this embodiment is also modified by a modification liquid, and the specific modification method is:

[0053] Preparation of modified solution:

[0054] 3-5 parts of silane coupling agent KH560 are added to 6-10 parts of chitosan solution with a mass fraction of 4-6%, and then 1-3 parts of yttrium nitrate solution with a mass fraction of 2% and 2-5 parts of nano-silicon dioxide modifier are added to fully mix to obtain a modified solution;

[0055] The coating source A and the modified liquid are stirred and modified in a weight ratio of 4:7. After the stirring is completed, the mixture is filtered and dried.

[0056] The preparation method of the nano-silicon dioxide modifier of the present embodiment is as follows: irradiate the nano-silicon dioxide in a proton irradiation box for 5-10 minutes, the irradiation power is 350W, and after the irradiation is completed, immerse the irradiated nano-silicon dioxide in a sufficient amount of 5% by mass lanthanum chloride solution for immersion treatment, and after the immersion is completed, filter and dry to obtain the nano-silicon dioxide modifier.

[0057] The immersion power of this embodiment is 350-400W, and the immersion time is 5-10 minutes.

[0058] The present embodiment provides a method for preparing a layered positive electrode material with a ternary gradient composite coating structure and its application in lithium-ion batteries.

[0059] Example 1

[0060] A method for efficiently preparing a positive electrode material for a lithium-ion battery, the specific steps are as follows:

[0061] 1) NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 Place in deionized water and stir to mix thoroughly, then dry in a blast drying oven at 150°C for 6 hours to obtain a mixed dry product I; wherein NiO, Co 3 O 4 、MnO 2 and Li 2 CO 3 The mass is measured according to the molar ratio of Li:Ni:Co:Mn=1.0:0.7:0.1:0.2.

[0062] 2) Evenly spread the material I into the boat-shaped sagger, and then place the sagger containing the material I in the middle of the plasma generator tube furnace, and then lock and seal the tube furnace device; open the oxygen valve connected to the plasma generator tube furnace, so that the material I in the generator tube furnace is in an oxygen atmosphere; wherein, the boat-shaped sagger is a high-temperature refractory ceramic sagger, the oxygen intake flow rate is 95 liters / min, and the tube furnace pressure is 25Pa;

[0063] 3) Plasma is generated by adjusting the power of the power supply and the gas flow rate (or gas pressure), and the temperature in the tube furnace is raised to 780°C and kept at this temperature for 90 minutes, and then the radio frequency power supply is turned off and the temperature is cooled to room temperature to obtain a single crystal ternary cathode material II;

[0064] 4) The single crystal ternary cathode material II and the coating source A are placed in deionized water and stirred and mixed evenly, and then dried in a blast drying oven at a temperature of 150° C. to obtain a mixed dried product III; wherein the coating source A is Al2O3 and TiO2, and the mass ratio thereof is 1.2:1.0, and Al 2 O 3 and TiO 2 The mass ratio of the single crystal ternary positive electrode material III is 0.17%; the coating source A includes but is not limited to Al 2 O 3 、Al(OH) 3 、TiO 2 , ZnO, Y 2 O 3 、MgO、WO 3 、ZrO、Co 3 O 4 One or more of the following;

[0065] 5) The dried material III is evenly spread into a boat-shaped sagger, and steps 2) and 3) are repeated to obtain a single crystal ternary positive electrode material IV; wherein the temperature in step 3) is 290° C. and the insulation time is 60 min; 6) The material IV is sieved, demagnetized, and packaged to obtain the final product.

[0066] Example 2

[0067] A highly efficient preparation method for a lithium-ion battery positive electrode material, the specific steps are as follows: similar to the preparation method in Example 1, the main difference is that: step 4) the coating method of the coating source A is different, specifically as follows: the single crystal ternary positive electrode material II and the coating source A are fully and evenly stirred by a traditional dry mixing method, heated to 290°C in a high-temperature box furnace and kept warm for 60 minutes to react, then cooled and sieved to obtain material IV; wherein the amount of coating source A used is the same as that in step 4) in Example 1.

[0068] Example 3

[0069] The preparation method is similar to that of Example 1, except that the mixing method and calcination method in steps 1), 2) and 3) are different, specifically as follows: NiO, Co3O4, MnO2 and Li2CO3 are placed in a mixing tank, and stirred thoroughly and uniformly according to the traditional dry mixing method, and then heated to 400 °C.

[0070] The temperature was raised to 910°C in a box-type furnace and kept for 10 hours to react, then cooled and sieved to obtain single crystal ternary positive electrode material II; wherein the masses of NiO, Co3O4, MnO2 and Li2CO3 were measured according to the molar ratio of Li:Ni:Co:Mn=1.0:0.7:0.1:0.2.

[0071] Example 4

[0072] The preparation method is similar to that of Example 1, except that the mixing method in step 1) is different, specifically as follows: NiO, Co3O4, MnO2 and Li2CO3 are placed in a mixing tank, and are fully stirred in accordance with the traditional dry mixing method to obtain a mixed dry product I; the remaining steps are exactly the same as those of Example 1

[0073] Example 5

[0074] The preparation method is similar to that of Example 1, with the main difference being that in step 4), the coating source A is Al2O3, and the amount used is the same as that in step 4) of Example 1.

[0075] Example 6

[0076] The preparation method is similar to that of Example 1, with the main difference being that in step 4), the coating source A is TiO2, and the amount used is the same as that in step 4) of Example 1.

[0077] Example 7

[0078] The preparation method is similar to that of Example 1, with the main difference being that the experimental operations of step 4) and step 5) are not performed.

[0079] In comparative example 1, a single crystal ternary positive electrode material II is obtained according to the dry mixing method and calcination method in Example 3; the obtained single crystal ternary positive electrode material II and the coating source A are fully and evenly stirred by a traditional dry mixing method, heated to 550°C in a high-temperature box furnace and kept warm for 6 hours to react, then cooled and sieved to obtain material IV; wherein the amount of coating source A used is the same as in step 4) in Example 1.

[0080] In comparative example 2, the single crystal ternary positive electrode material II is obtained as the final prepared sample by the dry mixing method and roasting method in Example 3, and the next coating process is not performed.

[0081] Optimization example 1;

[0082] On the basis of Example 1;

[0083] The coating source A is also modified by a modification liquid, and the specific modification method is as follows:

[0084] Preparation of modified solution:

[0085] 4 parts of silane coupling agent KH560 are added to 8 parts of chitosan solution with a mass fraction of 5%, and then 2 parts of yttrium nitrate solution with a mass fraction of 2% and 3.5 parts of nano-silicon dioxide modifier are added to fully mix to obtain a modified solution;

[0086] The coating source A and the modified liquid are stirred and modified in a weight ratio of 4:7. After the stirring is completed, the mixture is filtered and dried.

[0087] The preparation method of the nano-silicon dioxide modifier is as follows: irradiate the nano-silicon dioxide in a proton irradiation box for 7.5 minutes, the irradiation power is 350W, and after the irradiation is completed, immerse the irradiated nano-silicon dioxide in a sufficient amount of 5% by mass lanthanum chloride solution for immersion treatment, and after the immersion is completed, filter and dry to obtain the nano-silicon dioxide modifier. The immersion power is 370W and the immersion is 7.5 minutes.

[0088] Optimization example 2;

[0089] On the basis of Example 1;

[0090] The coating source A is also modified by a modification liquid, and the specific modification method is as follows:

[0091] Preparation of modified solution:

[0092] 3 parts of silane coupling agent KH560 are added to 6 parts of chitosan solution with a mass fraction of 4%, and then 1 part of yttrium nitrate solution with a mass fraction of 2% and 2 parts of nano-silicon dioxide modifier are added to fully mix to obtain a modified solution;

[0093] The coating source A and the modified liquid are stirred and modified in a weight ratio of 4:7. After the stirring is completed, the mixture is filtered and dried.

[0094] The preparation method of the nano-silicon dioxide modifier is as follows: irradiate the nano-silicon dioxide in a proton irradiation box for 5 minutes, the irradiation power is 350W, and after the irradiation is completed, immerse the irradiated nano-silicon dioxide in a sufficient amount of 5% by mass lanthanum chloride solution for immersion treatment, and after the immersion is completed, filter and dry to obtain the nano-silicon dioxide modifier. The immersion power is 350W and the immersion is 5 minutes.

[0095] Optimization example 3;

[0096] On the basis of Example 1;

[0097] The coating source A is also modified by a modification liquid, and the specific modification method is as follows:

[0098] Preparation of modified solution:

[0099] 5 parts of silane coupling agent KH560 are added to 10 parts of chitosan solution with a mass fraction of 6%, and then 3 parts of yttrium nitrate solution with a mass fraction of 2% and 5 parts of nano-silicon dioxide modifier are added to fully mix to obtain a modified solution;

[0100] The coating source A and the modified liquid are stirred and modified in a weight ratio of 4:7. After the stirring is completed, the mixture is filtered and dried.

[0101] The preparation method of the nano-silicon dioxide modifier is as follows: irradiate the nano-silicon dioxide in a proton irradiation box for 10 minutes, the irradiation power is 350W, after the irradiation, immerse the irradiated nano-silicon dioxide in a sufficient amount of 5% by mass lanthanum chloride solution for immersion treatment, after the immersion, filter and dry to obtain the nano-silicon dioxide modifier. The immersion power is 3400W, and the immersion is 5-10 minutes.

[0102] Table 1 lists the comparison of the electrical performance data of button cells made of the positive electrode materials of lithium-ion secondary batteries obtained in Examples 1 to 7 and Comparative Examples 1 to 2. Test of button cells: LR2032 button cells were made for testing. 1. First specific capacity and DCR test: Under 25±2°C, the button cell was charged to 4.5V at a constant current of 0.1C, charged to 0.05C at a constant voltage of 4.5V, and then discharged to 3.0V at a constant current of 0.1C; 2. High temperature cycle test: Under 45±2°C, the button cell was charged to 4.5V at a constant current of 0.5C, charged to 0.05C at a constant voltage of 4.5V, and then discharged to 3.0V at a constant current of 1.0C. The charging and discharging equipment used was a Blue Electric charging and discharging instrument.

[0103] The product performance tests of Examples 1-7, Comparative Examples 1-2 and Optimized Examples 1-3 are as follows:

[0104]

[0105]

[0106] Performance test of optimization example 1 and comparative example 1:

[0107]

[0108] According to the data of the embodiments and comparative examples in Table 1 Figure 2 , Figure 3 It can be seen that the single crystal ternary cathode material prepared by the present invention has a good morphology structure, and has a high specific capacity, first efficiency, low first DC-IR, high cycle retention rate and low cycle DC-IR growth rate; In addition, the electron microscope photo of the single crystal ternary cathode material prepared by Optimization Example 1 Figure 2 It can also be seen that the surface of the positive electrode material particles is smooth, round and uniform, indicating that the positive electrode material prepared by plasma technology has a high degree of single crystallization, a stable crystal structure, and a dense and uniform surface coating. Therefore, it has the best electrochemical performance, that is, the highest initial specific capacity and initial efficiency, low DC-IR, the highest cycle capacity retention rate and the lowest cycle DC-IR growth rate;

[0109] It can be seen from Optimization Examples 1-3 that the performance of the product is further improved after the product is optimized and improved by the specific method of the present invention.

[0110] from Figure 4 As can be seen from Table 2, the single crystal ternary cathode material prepared by low temperature plasma technology has a better layered structure and crystallinity. At the same time, the I003 / I104 value of the single crystal material prepared by low temperature plasma technology is significantly greater than that prepared by the traditional high temperature solid phase method. The purpose of full mixing is achieved by fully stirring and dissolving a variety of raw materials in deionized water, so that different elements can be efficiently and orderly crystallized during the plasma source roasting process to form a highly stable and orderly layered structure.

[0111] By calcining the positive electrode material through low-temperature plasma technology, the calcination temperature and calcination time can be greatly reduced, and the degree of single crystallization and crystal structure stability of the material can be improved, thereby improving the electrochemical performance; by coating with low-temperature plasma technology, a uniform and dense coating layer is formed on the surface of the particles, which effectively blocks the erosion of the electrolyte on the active substances of the matrix during the electrochemical process, prevents the failure of the matrix material, and improves the electrochemical performance.

[0112] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0113] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a layered positive electrode material with a ternary gradient composite coating structure, characterized in that: The following steps are involved: (1) NiO, Co3O4, MnO2 and Li2CO3 are placed in deionized water and stirred and mixed thoroughly, and then dried in a blast drying oven to obtain a mixed dry product I; wherein the masses of NiO, Co3O4, MnO2 and Li2CO3 are measured according to the molar ratio of the prepared ternary positive electrode material; the drying temperature in the blast drying oven is 120° C. to 180° C., and the drying time is 4 h to 8 h; (2) placing the dried object I in a plasma generator tube furnace device; (3) generating plasma by adjusting the frequency and power of the radio frequency power supply, raising the temperature in the tube furnace to 700° C. to 850° C. and maintaining the temperature for 30 min to 180 min, then turning off the radio frequency power supply and cooling the temperature to room temperature to obtain a single crystal ternary cathode material II; (4) placing the single crystal ternary cathode material II and the coating source A in deionized water, stirring and mixing them evenly, and then drying them in a forced air drying oven to obtain a mixed dried product III; (5) evenly spreading the dried material III into a boat-shaped sagger, and repeating steps 2) and 3) to obtain a single crystal ternary positive electrode material IV; wherein the temperature in step 3) is 200° C. to 350° C., and the holding time is 20 min to 120 min; (6) Screening, demagnetizing and packaging the material IV to obtain the final product.

2. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 1, characterized in that: The drying temperature in step 1) is 150° C. and the drying time is 6 hours; the masses of NiO, Co3O4, MnO2 and Li2CO3 are measured according to the molar ratio of Li:Ni:Co:Mn=0.7:0.1:0.2:1.

0.

3. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 2, characterized in that: The specific operation steps of placing the dried object I in the plasma generator tube furnace device are: Evenly spread it into the boat-shaped sagger, and then place the sagger containing material I in the middle position of the plasma generator tube furnace, and then lock and seal the plasma generator tube furnace device; open the oxygen valve connected to the plasma generator tube furnace to make the material I in the generator tube furnace in the oxygen atmosphere; wherein, the boat-shaped sagger is a high-temperature refractory ceramic sagger, the oxygen intake flow rate is 10 to 200 liters / min, and the tube furnace pressure is 0Pa to 30Pa.

4. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 3, characterized in that: The oxygen inlet flow rate is 95 liters / min, and the tube furnace pressure is 25 Pa; the temperature in the tube furnace in step 3) is raised to 780° C. and kept at this temperature for 90 minutes.

5. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 4, characterized in that: in, The coating source A includes but is not limited to one or more of Al2O3, Al(OH)3, TiO2, ZnO, Y2O3, MgO, WO3, ZrO, and Co3O4, and the mass ratio of the coating source A to the single crystal ternary positive electrode material III is 0.05% to 0.50%.

6. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 5, characterized in that: The coating source A is Al2O3 and TiO2; the mass ratio of Al2O3 to TiO2 is 1.2:1.0, and the mass ratio of Al2O3 and TiO2 to the single crystal ternary positive electrode material III is 0.17%; In step 5), the temperature in the tube furnace is raised to 290° C. and kept at this temperature for 60 min.

7. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 5, characterized in that: The coating source A is also modified by a modification liquid, and the specific modification method is as follows: Preparation of modified solution: 3-5 parts of silane coupling agent KH560 are added to 6-10 parts of chitosan solution with a mass fraction of 4-6%, and then 1-3 parts of yttrium nitrate solution with a mass fraction of 2% and 2-5 parts of nano-silicon dioxide modifier are added to fully mix to obtain a modified solution; The coating source A and the modified liquid are stirred and modified in a weight ratio of 4:

7. After the stirring is completed, the mixture is filtered and dried.

8. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 7, characterized in that: The preparation method of the nano silicon dioxide modifier comprises the following steps: irradiating the nano silicon dioxide in a proton irradiation box for 5-10 minutes, the irradiation power being 350W, immersing the irradiated nano silicon dioxide in a sufficient amount of 5% by mass lanthanum chloride solution for immersion treatment, filtering and drying after the immersion, and obtaining the nano silicon dioxide modifier.

9. The method for preparing a layered positive electrode material with a ternary gradient composite coating structure according to claim 8, characterized in that: The immersion power is 350-400W and the immersion time is 5-10min.

10. Application of the method for preparing a layered positive electrode material with a ternary gradient composite coating structure as claimed in any one of claims 1 to 9 in lithium-ion batteries.